The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5964/ejop.v15i3.1794
|View full text |Cite
|
Sign up to set email alerts
|

How to get rid of the belief bias: Boosting analytical thinking via pragmatics

Abstract: The previous research attempts to reduce the influence of the belief bias on deductive thinking have often been unsuccessful and, when they succeeded, they failed to replicate. In this paper, we propose a new way to see an old problem. Instead of considering the analytical abilities of the respondent, we focus on the communicative characteristics of the experimental task. By changing the pragmatics into play through a subtle manipulation of the instruction of the syllogism problem, we obtained a strong improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
3
0
1
Order By: Relevance
“…For instance, in recent studies on deductive reasoning with syllogisms and material implication (Macchi et al, 2019(Macchi et al, , 2020, we showed that, in adults, poor performance in logic tasks is not necessarily caused by poor logical abilities. Rather, it is caused by the lack of clear communication between the experimenter and participants.…”
Section: Introductionmentioning
confidence: 71%
“…For instance, in recent studies on deductive reasoning with syllogisms and material implication (Macchi et al, 2019(Macchi et al, , 2020, we showed that, in adults, poor performance in logic tasks is not necessarily caused by poor logical abilities. Rather, it is caused by the lack of clear communication between the experimenter and participants.…”
Section: Introductionmentioning
confidence: 71%
“…The literature on reasoning and decision making offers numerous examples in which behaviors or responses given by participants, initially judged to be erroneous, reveal a coherence with respect to the inferred representation of the participants to the requested task. These representations can be explained by the different pragmatic implicatures coming from the violations of the conversational maxims of cooperation of Grice ( 1975 ) (see Dulany and Hilton, 1991 ; Schwarz et al, 1991 ; Sperber et al, 1995 ; Baratgin and Noveck, 2000 ; Macchi, 2000 ; Politzer and Macchi, 2000 ; Baratgin, 2002 , 2009 ; Bagassi and Macchi, 2006 ; Baratgin and Politzer, 2006 , 2007 , 2010 ; Macchi and Bagassi, 2012 ; Politzer, 2016 ; Macchi et al, 2019 , 2020 ; Bagassi et al, 2020 ; Baratgin et al, 2020 , for examples). The experimental paradigms are constructed through speech acts and the gestures of the experimenter and are, as in any communication fact, pragmatic in nature (Sperber and Wilson, 1986 , 2002 ).…”
Section: The Ambiguity Of the Exchange Questionmentioning
confidence: 99%
“…(2) un efecto de validez lógica, en tanto se aceptan más argumentos válidos que inválidos, lo cual da cuenta de la capacidad de los participantes para razonar lógicamente y (3) una interacción entre lógica y creencia, en tanto el sesgo de creencia es significativamente superior cuando se razona con silogismos inválidos (Evans et al, 1983;Evans et al, 2001;Klauer, Musch y Naumer, 2000;Macchi et al, 2019;Morley et al, 2004;Stupple y Ball, 2008;Thompson et al, 2003).…”
Section: Aspectos Destacados Del Trabajounclassified